Network analysis and experimental validation to investigate chenpi against functional dyspepsia through TLR4/MyD88 by regulating the gut microbial structure - Jinfang Hu; Jinfang Hu; Xu Wang; Xiaoqiu Guo; Wen Wen; Jin Xue; Zhengzheng Liao; Zhengzheng Liao; Lihua Chen (Frontiers in Pharmacology)
Functional dyspepsia (FD) is a prevalent functional gastrointestinal disorder characterized by the absence of organic lesions; it affects nearly one-fifth of the global population. There is currently no specific drug for treating it. Citri reticulatae Pericarpium (CRP) has been utilized in China for millennia as a therapeutic agent for alleviating bloating and spleen–stomach disharmony. Nonetheless, the curative efficacy and precise molecular mechanisms implicated in FD warrant further investigation. This study aims to address this gap by investigating the potential mechanisms of CRP against FD using HPLC-ESI-QTOF-MS, network analysis prediction, and experimental validation. In this study, 90 CRP metabolites were identified by HPLC-ESI-QTOF-MS; 70 common targets of CRP and FD were extracted, and the top ten overlapped targets included MAPK1, MAPK2, and MAPK3. KEGG enrichment analysis revealed that the MAPK pathways were predominant and involved the TLR4 signaling pathway. In vivo experiments demonstrated that after 14 days of treatment, CRP improved body weight, gastric emptying rate, intestinal transit rate, and the pathological structure of the gastric tissue. Serum IL-6, TNF-α, and IL-1β were downregulated, and the expressions of TLR4, MyD88, p-NF-κB, and MAPKs were suppressed in gastric tissue. Furthermore, CRP increased the relative abundance of Patescibateria and Bacteroidota, accompanied by a reduction in the relative abundance of Verrucomicrobota and Proteobacteria. In brief, CRP could attenuate dyspepsia by reducing the activation of inflammation-related TLR4/MyD88 and MAPK signaling pathways and by mediating gut microbial structure and composition. This study provides a unique perspective for further research on drugs for treating FD.